Anti-Inflammatory and Chondro-Protective Effects of Acidic Polysaccharide from Enteromorpha Prolifera in Experimental Models of Osteoarthritis In-Vitro and In-Vivo. (December 2022) - Wang, Chih-Chien; Lu, Jeng-Wei; Chiang, Kuang-Hsing; Cheng, Yu-Shuan; Chu, You-Hsiang; Peng, Yi-Jen; Cheng, Chia-Hui; Chang, Chia-Yu; Chuu, Jiunn-Jye
Objective: Osteoarthritis (OA) progression has been shown to increase the expression of inflammatory cytokines in joints, leading to the destruction of cartilage matrix. Interleukin (IL)-1β is a potent inflammatory cytokine associated with osteoarthritic synovial fluid. The protective effects of polysaccharides from Enteromorpha prolifera against acute hepatic injury was reported. Design: In this study, we examined the effects of Enteromorpha polysaccharide extracts (EPEs) in the treatment of OA. The effects of the EPEs were assessed using an IL-1β-stimulated SW1353 and SW982 cells. The expression levels of specific mRNA and proteins were evaluated using semi-quantitative reverse transcription polymerase chain reaction (sqRT-PCR) and western immunoblotting. An OA animal study involving C57BL/6J mice was also conducted to assess the effects on tactile sensitivity and anterior cruciate ligament transection (ACLT). Results: Acidic polysaccharide extract (APE) was shown to significantly reduce cytokine and chemokine mRNA levels in IL-1β-stimulated SW1353 and SW982 cells and attenuate the expression of proinflammatory cytokines and p38/AP-1 in SW1353 cells. APE was also shown to minimize the effect of osteolytic lesions in the knee joints of ACLT-induced osteoarthritic mice. Conclusions: APE is a potent inhibitor of joint degeneration associated with OA.